Effects of chlorantraniliprole residual on Helicoverpa zea in Bt and non‐Bt cotton. Issue 5 (26th January 2021) - Babu, Arun; Reisig, Dominic D; Pes, Maiquel P; Ranger, Christopher M; Chamkasem, Narong; Reding, Michael E
Abstract: BACKGROUND: Helicoverpa zea is managed with foliar applications of chlorantraniliprole in cotton varieties that do not express the Vip3Aa19 toxin in the US Cotton Belt. Foliar insecticides and Bt could interact to influence larval susceptibility. Therefore, it has been suggested that chlorantraniliprole can be used as a tool for Bt resistance management. We designed field and laboratory studies to test the hypothesis that the interaction of Bt toxin and chlorantraniliprole application would result in lower H. zea larval survival when compared to the individual effect of Bt or chlorantraniliprole alone. We also tested for these interactions over time, since chlorantraniliprole residual has not been studied in cotton. RESULTS: Results from two field experiments and two laboratory experiments were similar. We found no interactions with Bt and chlorantraniliprole using data not corrected for natural mortality in untreated plots, indicating that these factors did not interact to influence survival. Moreover, we found that Bt and chlorantraniliprole did not interact to influence larval weight and instar. Chlorantraniliprole had lethal and sublethal effects on H. zea larval growth parameters feeding on cotton leaves up to 22 days after application, the final time period that we tested. Finally, concentration of chlorantraniliprole in the leaf was associated with larval survival for the duration of this study, but not larval growth or instar. CONCLUSION: Our findings complement the recommendation to use chlorantraniliprole for managing H. zea in cotton, given its long‐residual effects. However, the utility of chlorantraniliprole as a Bt‐resistance management tool for H. zea remains unclear. © 2021 Society of Chemical Industry Abstract : Is there an interaction of Bt and chlorantraniliprole in cotton that impacts Helicoverpa zea larval survival and growth? Our study found little evidence to support this.